Genome Analysis of Two Pseudonocardia Phylotypes Associated with Acromyrmex Leafcutter Ants Reveals Their Biosynthetic Potential - Holmes, Neil A.; Innocent, Tabitha M.; Heine, Daniel; Bassam, Mahmoud Al; Worsley, Sarah F.; Trottmann, Felix; Patrick, Elaine H.; Yu, Douglas W.; Murrell, J. C.; Schiøtt, Morten; Wilkinson, Barrie; Boomsma, Jacobus J.; et al. (Frontiers in Microbiology, 2016)
The attine ants of South and Central America are ancient farmers, having evolved a symbiosis with a fungal food crop >50 million years ago. The most evolutionarily derived attines are the Atta and Acromyrmex leafcutter ants, which harvest fresh leaves to feed their fungus. Acromyrmex and many other attines vertically transmit a mutualistic strain of Pseudonocardia and use antifungal compounds made by these bacteria to protect their fungal partner against co-evolved fungal pathogens of the genus Escovopsis. Pseudonocardia mutualists associated with the attines Apterostigma dentigerum and Trachymyrmex cornetzi make novel cyclic depsipeptide compounds called gerumycins, while a mutualist strain isolated from derived Acromyrmex octospinosus makes an unusual polyene antifungal called nystatin P1. The novelty of these antimicrobials suggests there is merit in exploring secondary metabolites of Pseudonocardia on a genome-wide scale. Here we report a genomic analysis of the Pseudonocardia phylotypes Ps1 and Ps2 that are consistently associated with Acromyrmex ants collected in Gamboa, Panama. These were previously distinguished solely on the basis of 16S rRNA gene sequencing but genome sequencing of five Ps1 and five Ps2 strains revealed that the phylotypes are distinct species and each encodes between 11-15 secondary metabolite biosynthetic gene clusters (BGCs). There are signature BGCs for Ps1 and Ps2 strains and some that are conserved in both. Ps1 strains all contain BGCs encoding nystatin P1-like antifungals, while the Ps2 strains encode novel nystatin-like molecules. Strains show variations in the arrangement of these BGCs that resemble those seen in gerumycin gene clusters. Genome analyses and invasion assays support our hypothesis that vertically transmitted Ps1 and Ps2 strains have antibacterial activity that could help shape the cuticular microbiome. Thus, our work defines the Pseudonocardia species associated with Acromyrmex ants and supports the hypothesis that Pseudonocardia species could provide a valuable source of new antimicrobials.